Stakeholder Dynamics in Downstreaming in Indonesia; A Case Study of Nickel Mining - Achmad Nur Hidayat; Mohamad Fadhil Hasan (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
Indonesia possesses significant mineral resources, making it a crucial player in the global mining industry. This research aims to examine the interests of critical stakeholders including the government, mining companies, local populations, and environmental groups to ensure the long-term viability of the downstream mining sector. The study aims to identify the dynamics of relationships and interests. It reveals that conflicts of interest exist, and if not managed effectively, they may impede the industry's progress. However, there are opportunities for collaboration that, if maximized, can boost added value for all stakeholders, including enhancing the welfare of local communities. The consequences of this research include legislative recommendations to the Indonesian government for the establishment of more inclusive legislation and ways for businesses to improve their interactions with local communities and other stakeholders. The implications of this research include legislative recommendations to the Indonesian government for the establishment of more inclusive legislation, as well as ways businesses can improve their engagement with local communities and stakeholders.